Theorizing religion in digital games: perspectives and approaches - Heidbrink, Simone; Knoll, Tobias; Wysocki, Jan (Online - Heidelberg journal of religions on the internet, 2014)
The article makes a case for Cultural and Religious Studies to expand the focus of research on digital games which so far have been a mostly neglected field of study. By means of discussing theoretical, methodical and practical approaches by various scholars from different academic disciplines the authors show how religion in games can be analysed, contextualized and interpreted. From a Cultural Studies perspective, they describe the genesis of religious discourses in context of digital games (re)trace the lines of their construction, reception and (re)contextualization as well as the role of the actors within these frameworks. Following a short overview on the history of (computer) game research, practical perspectives and approaches to computer games analysis are taken into focus. The authors refer to the “text” (in the broadest meaning) of the medium, but also include terms like “aesthetic”, “gameplay”, “gameworlds” and “gaming culture” into their considerations. Furthermore the characteristics and interconnections of a game-immanent as well as an actor-centered approach are being highlighted. The discussion on theories is exemplified by many case studies. Digital games as artifacts of contemporary popular culture are as a matter of fact subject to religious discourses on many different levels and by a multitude of (human) actors. They reside and influence the social realities of people who play. Religion is an important factor in this context and so are digital games. To understand the relation between both is the task of this paper.